2022
DOI: 10.3390/vaccines10040633
|View full text |Cite
|
Sign up to set email alerts
|

Economic-Related Inequalities in Zero-Dose Children: A Study of Non-Receipt of Diphtheria–Tetanus–Pertussis Immunization Using Household Health Survey Data from 89 Low- and Middle-Income Countries

Abstract: Despite advances in scaling up new vaccines in low- and middle-income countries, the global number of unvaccinated children has remained high over the past decade. We used 2000–2019 household survey data from 154 surveys representing 89 low- and middle-income countries to assess within-country, economic-related inequality in the prevalence of one-year-old children with zero doses of diphtheria–tetanus–pertussis (DTP) vaccine. Zero-dose DTP prevalence data were disaggregated by household wealth quintile. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…DTP3 coverage is frequently used as an indicator of child health and of health system function and performance broadly, as it requires regular and timely interaction with routine health systems [ 23 , 24 ]. While DTP3 coverage remains a standard indicator globally, the prevalence of zero-dose children is an equally important indicator of immunization service equity [ 25 ]. Major global immunization initiatives including the Immunization Agenda 2030 and the Gavi Phase 5 strategy feature the theme of leaving no one behind, highlighting a need to identify children who do not receive immunizations and understand factors associated with immunization non-receipt [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTP3 coverage is frequently used as an indicator of child health and of health system function and performance broadly, as it requires regular and timely interaction with routine health systems [ 23 , 24 ]. While DTP3 coverage remains a standard indicator globally, the prevalence of zero-dose children is an equally important indicator of immunization service equity [ 25 ]. Major global immunization initiatives including the Immunization Agenda 2030 and the Gavi Phase 5 strategy feature the theme of leaving no one behind, highlighting a need to identify children who do not receive immunizations and understand factors associated with immunization non-receipt [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Major global immunization initiatives including the Immunization Agenda 2030 and the Gavi Phase 5 strategy feature the theme of leaving no one behind, highlighting a need to identify children who do not receive immunizations and understand factors associated with immunization non-receipt [ 26 , 27 ]. A wide range of factors are known to be associated with non- or under-vaccination, including poverty [ 25 , 28 ], remote rural residence [ 29 ], conflict [ 30 ], migration [ 31 ], homelessness, cultural marginalization, and, importantly, gender-related barriers [ 32 ]. Centering gender equity and considering gender-related factors in childhood immunization activities is, thus, crucial to ensure that no children are left behind.…”
Section: Introductionmentioning
confidence: 99%
“…First, this study focuses on changes in geographic inequalities at the second administrative level or higher, which results in representing only one of many critical factors that contribute to inequities in immunization delivery [ 19 ]. While geographic location can serve as a proxy for determinants also associated with location (e.g., district-level program funding levels, relative remoteness) [ 58 ], geography on its own cannot appropriately approximate the mechanisms by which gender, ethnicity, education, wealth, religious affiliation, and other individual, household, or community characteristics affect childhood vaccination [ 4 , 8 , 12 , 13 , 14 , 16 , 18 ]. It is also very possible that reductions in geographic inequalities do not consistently correspond with decreases in vaccination inequalities by these other key drivers of disparities across locations or do so consistently over time.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, a growing body of research has sought to assess characteristics of zero-dose children and their families or households, as well as potential drivers of high zero-dose prevalence at different geographic levels [ 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Past work has found that zero-dose children experience a higher odds of missing or lacking access to other types of primary care services [ 6 , 11 , 12 ], while their mothers were more likely to have no antenatal care visits and not deliver at a health facility [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial inequalities in child immunization coverage have been widely documented in LMICs. (5, 1013) Well-established determinants of coverage include maternal education, household wealth and geographical location, whereas inequalities according to the child’s sex are not so evident. (10–12, 14) Ethnic group affiliation(15, 16) and religion(16) are also determinants of vaccine coverage in some, but not all countries.…”
Section: Introductionmentioning
confidence: 99%